2018
DOI: 10.1111/rssa.12384
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Approach to Modelling Subnational Spatial Dynamics of Worldwide Non-State Terrorism, 2010–2016

Abstract: Summary Terrorism persists as a worldwide threat, as exemplified by the on‐going lethal attacks perpetrated by Islamic State in Iraq and Syria, Al Qaeda in Yemen and Boko Haram in Nigeria. In response, states deploy various counterterrorism policies, the costs of which could be reduced through efficient preventive measures. Statistical models that can account for complex spatiotemporal dependences have not yet been applied, despite their potential for providing guidance to explain and prevent terrorism. To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 132 publications
(262 reference statements)
0
26
0
1
Order By: Relevance
“…For instance, different types of response variables may be considered, such as spatiotemporal log-Gaussian Cox processes as considered in Yuan et al (2017). Similarly, models for data on a larger spatial scale such as global data may be fitted directly on the surface of the Earth without the need for a projection into two-dimensional space as applied in Python et al (2016) to model global terrorism in space and time. Using the joint modelling approach these models may be extended to a multispecies or to a multievent situation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, different types of response variables may be considered, such as spatiotemporal log-Gaussian Cox processes as considered in Yuan et al (2017). Similarly, models for data on a larger spatial scale such as global data may be fitted directly on the surface of the Earth without the need for a projection into two-dimensional space as applied in Python et al (2016) to model global terrorism in space and time. Using the joint modelling approach these models may be extended to a multispecies or to a multievent situation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, MCMC will take hours or days in order to successfully simulate from the posterior making the computational cost of fitting multiple process models extremely high. In Python et al (2016), terrorism data was fit using a grid over the entire planet using INLA, though without self-excitation in the model.…”
Section: Self-excitingmentioning
confidence: 99%
“…We will make the simplifying assumption that both of these are static over time. Previous statistical analysis on terrorism considered macro level covariates, such as democracy in Python et al (2016) that differ country to country but would not change within a single country as analyzed here. Other studies considered more micro level covariates such as road networks that were found to be statistically related to terrorism in Braithwaite and Johnson (2015).…”
Section: Spatio-temporal Diffusion Of Violence Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Early analyses explored these by using routine data and methods, novel at the time, that tweaked the existing multiple‐regression methods, by incorporating a measure of distance (Pocock et al ., ). Further work has evolved to be much more explicit about the spatial properties of the mapping and has been applied in diverse areas including forestry and terrorism (de Rivera et al ., ; Python et al ., ).…”
Section: Current Challengesmentioning
confidence: 99%